Degradation dynamics of glyphosate in two types of soil from corn fields of the Philippines - Mercado, C. A.; Mactal, A. G. (International Journal of Agricultural Technology, 2021)
Glyphosate degradation in two types of soils from corn fields in the Philippines was determined. The soils from two land mapping units showed different soil pH, CEC, soil organic matter and clay contents. These were planted with herbicide-ready corn variety for 16 years and are regularly applied with glyphosate. Initial analysis of soils in both LMU 1 and LMU 2 showed low level of glyphosate residue with a value of 0.01 mg/kg and is considered below the critical residue level for glyphosate of 0.1 mg/kg of soil. Glyphosate residue was analyzed at 1, 15 and 30 days after the application of 0.96 mg/kg of glyphosate in soils belonging to two LMUs. Results showed that glyphosate residue in the soil at 1 DAA decreased by 11.04 to 14.4 percent in LMU 1 and LMU 2 respectively. At 15 days after application, glyphosate residue continued to decline to 0.059 mg/kg for LMU 1 and 0.041 mg/kg for LMU 2. These values correspond to 93.85 to 95.73 % reduction from the initial level of 0.96 mg/kg. The amount of glyphosate at 30 DAA is detected below the limit of gas chromatography of 0.01 mg/kg. Glyphosate degradation for LMU 1 is represented by the equation y=-0.0329x+0.8488 with a correlation coefficient of 0.8391. On the other hand, glyphosate degradation for LMU 2 is represented by the equation y=-0.0324x+0.8299 with a correlation coefficient of 0.8254. Degradation was shown to be faster in soils with low organic matter, low clay content, low CEC and slightly alkaline (LMU 2). It showed that glyphosate is not as persistent as it is previously reported